2015
DOI: 10.3329/sja.v13i1.24190
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing nitrogen rate and planting density for sunflower under irrigated conditions of Punjab

Abstract: A field study was conducted at different nitrogen rates on growth, yield and achene oil content of sunflower sown at different planting densities at Faisalabad, Punjab, Pakistan. Randomized complete block design with split plot arrangement was applied, having plants densities (8.33, 6.67 and 5.56 plants m -2 ) in main plots and while various nitrogen levels (90, 120 and 150 kg ha -1 ) in sub-plots. The plant densities and various nitrogen levels had a significant effect on leaf area index, crop growth ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In the monoculture, head diameter in P45 was higher than in P90 (p<0.01): means of 13.23 and 11.09 cm, respectively. This difference in size was small, whereas in other studies involving populations of sunflowers, there were reductions between 4 and 14 cm in head diameter when the population was as twice as dense (Sedghi et al, 2008;Rasool et al, 2015).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…In the monoculture, head diameter in P45 was higher than in P90 (p<0.01): means of 13.23 and 11.09 cm, respectively. This difference in size was small, whereas in other studies involving populations of sunflowers, there were reductions between 4 and 14 cm in head diameter when the population was as twice as dense (Sedghi et al, 2008;Rasool et al, 2015).…”
mentioning
confidence: 67%
“…The data on yield components of sunflower offer further insights into these results ( Table 2). One of the components that most affect yield is head diameter, as it influences both achene size and number of achenes per head (Rasool et al, 2015). This characteristic was crucial for the occurrence of higher yields in the denser population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zubillaga et al [11] have showed that the sunflower biomass increased from 19 to 40% when an optimum nitrogen amount was applied. In addition, nitrogen fertilizer had positive effects on sunflower dry yield according to other researches [12,13]. On the other hand, nitrogen is considered to be one of the costliest inputs in agricultural management [14].…”
Section: Introductionmentioning
confidence: 99%
“…The highest seed weight head -1 with the geometry of 85 x 20 cm may be associated to optimum row and plant spacing. Planting densities caused positively significant impact on sunflower seed weight head -1 (Rasool et al, 2015).…”
mentioning
confidence: 99%